Happy Employees, High-Performing Company: Empathy-Based Management - Sundayana, Dendy; Rakhmanita, Ani; Artini, Yenny Dwi (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the effect of empathy-based management on employee job happiness and company performance, using a case study at PT Nusantara Almazia. A quantitative research approach was employed, utilizing a survey method involving 120 permanent employees from various divisions. The research instrument used was a Likert-scale questionnaire, and the data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that empathy-based management has a positive and significant effect on employees’ job happiness and both directly and indirectly contributes to improving company performance. Job happiness is proven to be a mediating factor that strengthens the relationship between managerial empathy and organizational performance. These findings emphasize the importance of emotional approaches in modern human resource management practices, particularly in the context of Indonesian work culture that values collectivism and interpersonal relationships. This study provides practical implications for companies in developing empathetic leadership training and creating a healthy and productive work culture.